2021
DOI: 10.1177/10775587211062403
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prediction of Long-Term Care Utilization Through Patient-Reported Measures: Cross-Sectional Analysis of High-Need U.S. Veterans Affairs Patients

Abstract: This article examines the relative merit of augmenting an electronic health record (EHR)-derived predictive model of institutional long-term care (LTC) use with patient-reported measures not commonly found in EHRs. We used survey and administrative data from 3,478 high-risk Veterans aged ≥65 in the U.S. Department of Veterans Affairs, comparing a model based on a Veterans Health Administration (VA) geriatrics dashboard, a model with additional EHR-derived variables, and a model that added survey-based measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To understand the prevalence of social risks and which risks might be predictive of outcomes in VA patients at high risk for hospitalization or death, the US Veterans Affairs (VA)'s Office of Primary Care conducted a mail survey in 2018 that included a comprehensive set of social, behavioral, and health measures. Prior analyses found that certain social risks predicted VA hospitalization, 6 ED use, 17 and long‐term care use, 18 but few studies have examined the association between social risks and health expenditures. In the current study, we examined the association between patient‐reported social and behavioral risks and VA expenditures across a broad range of Veteran‐reported social risks in a nationally representative sample of high‐risk Veterans who obtain VA healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the prevalence of social risks and which risks might be predictive of outcomes in VA patients at high risk for hospitalization or death, the US Veterans Affairs (VA)'s Office of Primary Care conducted a mail survey in 2018 that included a comprehensive set of social, behavioral, and health measures. Prior analyses found that certain social risks predicted VA hospitalization, 6 ED use, 17 and long‐term care use, 18 but few studies have examined the association between social risks and health expenditures. In the current study, we examined the association between patient‐reported social and behavioral risks and VA expenditures across a broad range of Veteran‐reported social risks in a nationally representative sample of high‐risk Veterans who obtain VA healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there has been no direct test of whether a 6‐month versus 12‐month look‐back period affects the prevalence of reported social risks. Furthermore, there is limited data on the prevalence of particular social risks among Veterans and their association with health 10–12 . The aims of this article are to compare the effects of 6‐ and 12‐month look‐back periods on the prevalence of reported social risks and to identify social risks that are correlated with overall health and mental health ratings among Veterans.…”
Section: Introductionmentioning
confidence: 99%